PENERAPAN PEMBELAJARAN PROBLEM-BASED LEARNING UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KREATIF MATEMATIS DAN MINAT BELAJAR PESERTA DIDIK - Risma Ardiwianti; Heru Sujiarto; Usep Kosasih (UJMES (Uninus Journal of Mathematics Education and Science), 2022)
The background of this research is the low ability of students to think creative mathematically and interest in learning mathematics in the learning process. The alternative learning that can be applied to improve the student’s Mathematical creative thinking ability and interest in learning mathematics is the Problem-Based Learning model. The aim of this research is to improve the student’s Mathematical creative thinking ability and interest in learning mathematics by using the Problem-Based Learning model. The research is classroom action research carried out in three cycles with research design including planning, action implementation, observation, and reflection. The research subjects were students of class VII E one of the schools in Bandung District. The data collection instruments used consisted of observation sheets, tests, questionnaires, and journals. The test results, questionnaires, and observations were analyzed using percentages. Based on the result of the analysis: The student’s mathematical creative thinking ability and interest in learning mathematics in class VII E one of the schools in Bandung District increased after learning by using the Problem-based learning model.